Rethinking the regulations and development patterns of villages connected to the city; approaches based on generic codes at macro level(Case study: Perjikola and Bala lamouk villages, Ghaemshahr city) - Hadi pendar (مسکن و محیط روستا)
Existing or new residential development on the exterior edges of the north cities does not pay much attention to the preserving spatial and morphological identity. A certain shape of identified morphology that was the result of segmentation and imparted in special type of figure-ground, has been neglected in new development and many of landscape quality are diminishing consequently. Gradual Shaping of neighborhoods in the context of local areas of north of Iran, has been greatly influenced by the indigenous identity. But the principles guiding the morphological identity of the settlements in the current developments have not been able to continue.  In the meantime, many villages have gradually become part of the urban areas, heavily influenced by urban development patterns and are losing their special identity. Since the development programs in rural areas are often by a design criteria similar to other parts of the city, the flourishing local identity does not seem very efficient. How to develop a gradual process that allows the development of residential blocks in a sustainable manner by keeping the unique social identity of the region, is the key question which this article is seeking for the answer of. Process based on generative codes based on flexibility, sustainability and evolution of the most fundamental features in action at the neighborhood scale. The research was conducted based on logical reasoning. Because transmission of quality of place, especially because of the gradual stabilization of morphological quality, well not take place. Scope of study is how the gradual formation of tissues in previously undeveloped land in villages linked to the ecological areas. Field studies villages "Bala Lamuk" and "Perjikola" north of the east-west belt has been Ghaemshahr is connected to the north, but during time has become semi urban texture. The theoretical framework of the research is based on the application of Christopher Alexander's theory to gradually growth based on the concept of generative codes. The first part of the research analysis the results of the existing standards by critical-analysis approach. In the second part, based on the process based on generative codes, the results are projected at the field study scope. The method of doing research is replication, which is accompanied by information gathering by documentary methods, morphological analysis, and systematic observation of the exiting situation. Based on the results of the research, the process of rural development in the areas under discussion can be formulated through a gradual and seven-step process based on generational codes and residents' participation. The result of this gradual process is the continuity of organic tissues that meet the previous qualities while being responsive to existing needs. Identifying authentic identities and areas requiring permanent protection, explaining generative codes based on existing needs and opportunities, gradually locating and enhancing participation, and collaborative design are the main steps in the proposed process of the present study.